Paradygmat i suspens. O dramaturgii scenariusza filmowego - Otto, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Paradigm and Suspense. Th e Dramaturgy of a Film Script Film scripts have a dramaturgical structure, i.e. a specific format comprising a particular number of scenes written in a predetermined order. Its vital elements are a three-act structure and two plot twists. It is also characterized by the development of tension, intended to lead to a constant rise in emotions as the story advances. The dramaturgy of the scenes and their sequence are built in many ways, the main two being suspense and delay. These are used to suspend action, slow it down in order to achieve an element of surprise, and to raise emotions in forthcoming scenes.